The impacts of foreign direct investment and export expansion on the performance of the high-tech manufacturing industry - Dyah Wulan Sari,; Wenny Restikasari,; Ajija, Shochrul Rohmatul; Islamia, Haura Azzahra Tarbiyah; Muchtar, Darmawati (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study investigates the impact of foreign direct investment and export expansion on firm performance. Using firmlevel data from the Indonesian high-tech manufacturing industry, we employ stochastic frontier analysis to determine firm efficiency. Our study provides evidence of negative backward and positive forward FDI spillovers on firms’ efficiency level. The results further show that foreign firms in the high-tech manufacturing industry are more efficient than local firms. Furthermore, a greater degree of fragmented trade integration is related to better performance among firm in the high-tech manufacturing industry. This indicates the significance of the production of component goods relative to the finished goods. In terms of the policy, the authority might need to consider whether the existence of FDI benefits local producers beyond promoting trading of component goods of the high-tech manufacturing industry.